Spatial and Temporal Distribution Characteristics and Source Apportionment of VOCs in Lianyungang City in 2018 - Cheng Chen; Lingrui Wang; Yunjiang Zhang; Shanshan Zheng; Lili Tang (Atmosphere, 2021)
From April to September 2018, five sampling sites were selected in Lianyungang City for volatile organic compounds (VOCs) analysis, including two sampling sites in the urban area (Lianyungang City Environmental Monitoring Supersite and Mine Design Institute), one sampling site in the industrial area (Deyuan Pharmaceutical Factory), and two sampling sites from the suburb (Hugou Management Office and YuehaiLou). The results showed that the mean VOCs concentration followed this pattern: industrial area (36.06 ± 12.2 µg m−3) > urban area (33.47 ± 13.0 µg m−3) > suburban area (27.68 ± 9.8 µg m−3). The seasonal variation of the VOCs trend in the urban and suburban areas was relatively consistent, which was different from that in industrial areas. The concentration levels of VOCs components in urban and industrial areas were relatively close, which were significantly higher than that in suburban areas. The possible sources and relative importance of VOCs in Lianyungang City atmosphere were measured by the characteristic ratio of toluene/benzene (T/B), ethane/acetylene (E/E) and isopentane/TVOCs. The contribution of traffic sources to the VOCs in Lianyungang City was significant (T/B ~ 2), and there were obvious aging phenomena in the five sampling sites (E/E > 4). The ratio of isopentane/TVOCs in the contribution of gasoline volatilization sources in urban and suburban areas was significantly bigger than that in industrial areas. According to the maximum incremental reactivity (MIR) method, aromatics (40.32–58.09%) contributed the most to ozone formation potential (OFP) at the five sampling sites. The top 10 OFP species showed that controlling n-hexane and aromatics, such as benzene, toluene, xylene, and trimethylbenzene in Lianyungang City can effectively control ozone generation. Nineteen typical VOCs components were selected and the sources of VOCs from five sampling points were analyzed by the principal component analysis (PCA) model. The sources of VOCs in different areas in Lianyungang were relatively consistent. Five sources were analyzed at the two sampling sites in the urban area: industrial emission + plants, vehicle exhaust, fuel evaporation, combustion and industrial raw materials. Four sources were analyzed in the industrial area: industrial emission + plants, vehicle exhaust, fuel evaporation and combustion. Five sources were analyzed at the two sampling sites in the suburban area: industrial emission + plants, vehicle exhaust, fuel evaporation, combustion and solvent usage.